Combined toxicity of heavy metal mixtures in liver cells. Issue 9 (10th February 2016) - Lin, Xialu; Gu, Yuanliang; Zhou, Qi; Mao, Guochuan; Zou, Baobo; Zhao, Jinshun
Abstract: With rapid industrialization, China is now facing great challenges in heavy metal contamination in the environment. Human exposure to heavy metals through air, water and food commonly involves a mixture consisting of multiple heavy metals. In this study, eight common heavy metals (Pb, Cd, Hg, Cu, Zn, Mn, Cr, Ni) that cause environmental contamination were selected to investigate the combined toxicity of different heavy metal mixtures in HL7702 cells. Toxicity (24 h LC50 ) of each individual metal on the cells ranked Hg > Cr = Cd > Cu > Zn > Ni > Mn > Pb; toxicity of the different mixtures ranked: M5 > M3PbHgCd > M5+Mn > M5+Cu > M2CdNi > M4A > M8‐Mn > M8 > M5+Zn > M4B > M8‐Cr > M8‐Zn > M8‐Cu > M8‐Pb > M8‐Cd > M8‐Hg > M8‐Ni > M3PbHgNi > M3CuZnMn. The cytotoxicity data of individual metals were successfully used to build the additive models of two‐ to eight‐component metal mixtures. The comparison between additive model and combination model or partly additive model was useful to evaluate the combined effects in mixture. Synergistic, antagonistic or additive effects of the toxicity were observed in different mixtures. These results suggest that the combined effects should be considered in the risk assessment of heavy metal co‐exposure, and more comprehensive investigations on the combined effects of different heavy metal mixtures are needed in the future. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Human exposure through air, water and food normally involves a mixture consisting of multiple metals. In this study, eight common heavy metals (Pb, Cd, Hg, Cu, Zn, Mn, Cr, Ni) that cause environmental contamination were selected to investigate the combined toxicity of different metal mixtures in HL7702 cells. Synergistic, antagonistic or additive effects of the toxicity were observed in different metal mixtures. These results suggest that the combined effects should be considered in the risk assessment of heavy metal co‐exposure.